ISTIQOMAH IN AL-QUR’AN: THE CONCEPT, TERMINOLOGY, AND IT’S APPLICATION - Achmad Ramadhan (UIN Sumatera Utara, 2020)
This paper is aimed to describe the most spoken concept in alQur’an, namely istiqomah and its application. The description of this important concept covers some aspects: 1) the definition and meaning of istiqomah both etimologically and terminologically, 2) the interpretations of the Muslim scholars dealing with the concept, 3) the answer to the question if it is the strange term to Muslim, 4) the significance of the implementation of the term istiqomah, and 5) the ways to implement the concept of istiqomah. Based on the descriptions above, it can be concluded that the concept of istiqomah covers some aspects as follows: 1) istiqomah deals with tauhid purity and not false worship, 2) istiqomah deals with doing the duties, either compulsory or optional, physically or mentally, 2) istiqomah deals with leaving out all the prohibitions, 3) istiqomah deals with being a pious to worship Allah The Almighty, 4) istiqomah deals with the continuation of worshipping Allah The Almighty, and 5) istiqomah deals with the implementation of the rightness in social life